The Moral Paradox of War: A Platonic Analysis of “The Man He Killed” by Thomas Hardy - Princess Sarah Camado; Sheana Rose Barbosa; Ana Mae Monteza (J-Lalite: Journal of English Studies, 2026)
This study offers a Platonic analysis of “The Man He Killed” by Thomas Hardy, examining the moral paradoxes of war through the lens of Plato’s Tripartite Theory of the Soul or Moral Psychology. The research investigates how the poem’s speaker experiences internal conflict among reason (logistikon), spirit (thymoeides), and appetite (epithymia), highlighting the psychological fragmentation caused by war. The objective is to explore how Hardy uses irony, everyday language, and flawed reasoning to question the ethical excuses people make for violence and to highlight deeper philosophical issues about justice and moral responsibility. Using a qualitative interpretive method grounded in Platonic moral philosophy, the study finds that war disrupts the soul’s harmony, illustrating how individuals may act against rational moral instincts due to social duty, honor, and economic coercion. These insights deepen the understanding of Hardy’s anti-war message and support Sustainable Development Goals 16 (Peace, Justice, and Strong Institutions) and 4 (Quality Education) by promoting ethical reflection and peace education through literature. Ultimately, the study underscores how poetic language can serve as a powerful medium for exposing moral contradictions and fostering critical engagement with issues of violence and justice.